The influence of using word search learning media on students' Javanese cultural knowledge - Mardhiyah, Ainaul; Zulaili, Iin Nur; Laili Rahmawati; Taufik'an Hidayah (Jurnal Bidang Pendidikan Dasar, 2024)
Learning media plays an important role in the teaching and learning process, supporting teachers in delivering material more effectively. Javanese at Madrasah Ibtidaiyah is a challenge because many students do not know these terms. His rejection of Javanese culture gave rise to a negative view of cultural performances that were considered ancient. To overcome this problem, Android-based word search media is presented as a solution to make it easier for students to understand Javanese culture. This game involves arranging random letters into the correct Javanese Cultural word. The assessment instrument used in this research is the quasi-experimental pretest-posttest control group design method. The results of research at MI Ma'hadut Thullab showed a significant increase in the class average score, namely reaching 83,200 after using word search media, while students who did not use word search media only obtained an average learning outcome score of 48,583.